Effect of Sodium Hypochlorite and Glutaraldehyde on Hardness of Calcium Sulphate Hemihydrate: Sodium Hypochlorite and Glutaraldehyde on Hardness of Calcium Sulphate Hemihydrate - Abbas, Mahrukh; Shaikh, Irfan Ahmed; Memon, Abdul Bari; Permanand, .; Ahmed, Muhammad; Shaikh, Usman Bashir; Bhellar, Ghazanfar Ali (Pakistan Journal of Health Sciences, 2024)
Calcium sulphate hemihydrate (CSH) is extensively used in dentistry for impressions, models, and casts due to its versatility. However, exposure to disinfectants like sodium hypochlorite and glutaraldehyde, commonly used in dental practices, can potentially alter CSH’s mechanical properties. Objective: To measure the hardness of calcium sulphate hemihydrate cast after repeated immersion in sodium hypochlorite and glutaraldehyde solutions. Methods: This cross-sectional study was conducted at the Department of Prosthodontics, Institute of Dentistry LUMHS, Jamshoro and the Department of Mechanical Engineering, Institute of Mehran University of Engineering and Technology, Jamshoro. Test groups were divided into three groups i.e. Control group, Sodium hypochlorite (0.525%) and Glutaraldehyde (2%). Descriptive statistics were calculated. Results: Mean hardness in Group A was 8.94 ± 0.40, 8.40 ± 0.47 in Group B and 8.02 ± 0.59 in Group C. The mean hardness at the load of 10 kg in Group A, Group B and Group C was 7.01 ± 0.05, 7.31 ± 0.25, and 7.06 ± 0.04 respectively. Mean hardness at a secondary load of 60 kg in Group A, Group B and Group C was 6.95 ± 1.21, 7.48 ± 0.24 and 7.24 ± 0.05 respectively. The results showed a significant mean difference for mean hardness (p = 0.000), hardness at the load of 10 kg (p = 0.000) and hardness at the secondary load of 60 kg (p = 0.036). Conclusion: It was concluded that mean hardness was more in sodium hypochlorite group than control group and glutaraldehyde group